Short Communication: Hepatoprotective effect of methanol extract of sambiloto leaves (Andrographis paniculata) against malondialdehyde levels in liver tissues of paracetamol-induced Wistar rat - ANDRIANI ANDRIANI; VIRHAN NOVRIANY; GUNTUR SUSENO; EFFIANA EFFIANA; IIT FITRIANINGRUM (Smujo International, 2018)
Andriani, Suseno G, Effiana, Novriany V, Fitrianingrum I. 2018. Short Communication: Hepatoprotective effect of methanol extract of sambiloto leaves (Andrographis paniculata) against malondialdehyde levels in liver tissues of paracetamol-induced Wistar rat. Nusantara Bioscience 10: 87-90. Andrographis paniculata contains andrographolide and flavonoids, which have a hepatoprotective effect. This study was aimed to examine hepatoprotective effect of Andrographis paniculata extract against liver tissues malondialdehyde (MDA) levels of paracetamol induced Wistar rat (Rattus novegicus). The study was designed with posttest-only control group conducted at Tanjungpura University, Indonesia in June 2015. A total of 30 rats at age of three weeks were divided into 6 groups. They were given toxic dose paracetamol, curcumin and A. paniculata extract in different dose. Liver tissues were tested by Wills’s method. The data was analyzed using One-way ANOVA and LSD Post-hoc test. MDA levels of liver tissues were i.e, normal control (0.34 nmol mL-1), positive control (0.34 nmol mL-1), dose 1 (0.45 nmol mL-1), dose 2 (0.55 nmol mL-1), dose 3 (0.63 nmol mL- 1 ), negative control (1.32 nmol mL-1). Result showed that MDA levels of liver tissues of negative control group were significantly different with other groups (ANOVA, p? 0.05). There were no significant differences between MDA levels of liver tissues of Dose 1 with normal control and positive control (ANOVA, p>0.05). The methanol extract of A. paniculata has a hepatoprotective effect in (MDA) levels of paracetamol-induced Rattus novegicus with an effective dose of 500 mg kg-1.